2022
DOI: 10.3233/wor-210819
|View full text |Cite
|
Sign up to set email alerts
|

How does the working environment transition impact perceived work-related quality of life for postsecondary teachers within the United States?

Abstract: BACKGROUND: The COVID-19 pandemic has profoundly affected societal norms and shifted much of the workforce in the United States to a virtual landscape. Working and learning from home (or “remotely”) has become common in nearly every field, including higher level education. Each institution has implemented policies regarding remote work, and with the different policies educators are confronted with different conditions which affect their perceived level of stress and quality of working life. OBJECTIVE: The obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In the wake of COVID-19 and the rapid move toward remote work, there has been extensive discussion regarding WLB for remote workers (e.g. Dandalt, 2021; Horton and Jacobs, 2022). While studies have shown that WLB became difficult in the height of the pandemic (Horton and Jacobs, 2022; Palumbo, 2020), studies have also shown that for some working remotely led to greater flexibility and better WLB (Dandalt, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the wake of COVID-19 and the rapid move toward remote work, there has been extensive discussion regarding WLB for remote workers (e.g. Dandalt, 2021; Horton and Jacobs, 2022). While studies have shown that WLB became difficult in the height of the pandemic (Horton and Jacobs, 2022; Palumbo, 2020), studies have also shown that for some working remotely led to greater flexibility and better WLB (Dandalt, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Dandalt, 2021; Horton and Jacobs, 2022). While studies have shown that WLB became difficult in the height of the pandemic (Horton and Jacobs, 2022; Palumbo, 2020), studies have also shown that for some working remotely led to greater flexibility and better WLB (Dandalt, 2021). The current study complements this research by showing that the benefits of remote work may hinge on leader behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations